NAECON 2014 - IEEE National Aerospace and Electronics Conference 2014
DOI: 10.1109/naecon.2014.7045775
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution imaging by arrays of high-index spheres embedded in transparent matrices

Abstract: We fabricated thin-films made from polydimethylsiloxane (PDMS) with embedded high-index (n~1.9-2.2) microspheres for super-resolution imaging applications. To control the position of microspheres, such films can be translated along the surface of the nanoplasmonic structure to be imaged. Microsphere-assisted imaging, through these matrices, provided lateral resolution of ~λ/7 in nanoplasmonic dimer arrays with an illuminating wavelength λ=405 nm. Such thin films can be used as contact optical components to boo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…However, as the lubricant evaporates, the resolution gradually increases beyond the diffraction limit. The resolution ∼ λ /7 obtained by this technology was first observed and studied in . After that, a resolution limited at ∼ λ /4 by non‐movable coverslips was reported in .…”
Section: Introductionmentioning
confidence: 97%
“…However, as the lubricant evaporates, the resolution gradually increases beyond the diffraction limit. The resolution ∼ λ /7 obtained by this technology was first observed and studied in . After that, a resolution limited at ∼ λ /4 by non‐movable coverslips was reported in .…”
Section: Introductionmentioning
confidence: 97%
“…Many novel optical properties of a microsphere lens such as photonic nanojets [1][2][3], whisper gallery modes [4], Poynting field [5,6], light compression [7], and super-resolution imaging [8][9][10][11][12][13][14][15][16][17] have been observed. Microsphere-assisted microscopy is a simple and effective approach to obtain super-resolution imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a high refractive index microsphere presents many advantages in prefabrication and location movement because it can be embedded in transparent solidified films used as cover slips to observe the samples [10]. Darafsheh et al have observed the radiation-induced glioblastoma cells using a high index microsphere embedded in elastomers [7].…”
Section: Introductionmentioning
confidence: 99%
“…To develop a novel optical component for enhancing a microscope's resolution, we fabricated polydimethylsiloxane (PDMS) slabs, with embedded high-refractive-index barium titanate microspheres. [17][18][19] We have also shown-for the first timethat these slabs can provide optical super-resolution imaging, as well as a surface scanning capability. [17][18][19] Our PDMS slabs-see Figure 2(a)-adhere to the surface of nanoplasmonic structures, which results in imaging of gold dimers and bowties with a resolution of about /6-/7.…”
Section: 1117/21201601006314 Page 3/4mentioning
confidence: 99%
“…We have shown, however, that this approach can provide overestimated resolution values and have developed a more rigorous quantification of super-resolution. [17][18][19][20][21] This method is based on a convolution of the arbitrarily shaped objects with the 2D point spread function (PSF). Although this is a standard far-field…”
mentioning
confidence: 99%